The Relationship between Selected Training Methods and Employee Performance in Kuching Manufacturing Sector - Nor Hazlin, Toni (Universiti Malaysia Sarawak (UNIMAS), 2021)
The aim towards this research is to investigate the relationship between selected training methods and employee performance in Kuching manufacturing sector. The on-the-job training, off-the-job training, and induction training was selected as the dependent variable and employee performance as the independent variable in this research. The quantitative methodology was used to obtain the required information for this research. The nature population of this study was among employees in the manufacturing sector that is in HGST Malaysia Sdn. Bhd. and LonGi (Kuching) Sdn. Bhd. Therefore, in this research, a total of 94 employees from both companies were chosen as respondents. As the instrument, this research used the survey questionnaire through Google Form to collect the data. The data then were analyzed by using descriptive and inferential statistics. In this research, the Spearman Correlation and Multiple Regression of data analysis is being used. Spearman Correlation analysis is used to identify the relation between the independent variables (on-the-job training, off-the-job training, and induction training) and the dependent variable (employee performance). Meanwhile Multiple Regression was used to determine which training methods become more dominant and affecting employee performance. The findings shown that there is a moderate relationship between selected training methods and employee performance in Kuching manufacturing sector. As for the dominant training methods, it can be concluded that, induction training has become the most dominant factor among the independent variables that influences the employee performance in Kuching manufacturing sector. Therefore, from this type of findings, it would help the HR practitioners or even the manager itself in manufacturing sector to focus more on the induction training, in order to enhance the employee performance as well as their productivity in workplace.